Standardization and Adaptation In International Marketing: A Conceptual Review And Intergrative Framework - Stefani Angmalisang; Tatia Panese; Maribell Zachawerus; Abdilah Makausi; Jonathan Kaeng; Bayula Sabuda; Yusmadi Damopolii; Febby Pitoy; Nickstel Assa; Dwi Patra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
Global marketing has long faced the strategic challenge of balancing global brand consistency with the need for local market responsiveness. This study aims to conceptually explore how international firms integrate standardization and adaptation strategies within the ongoing digital transformation era. Using a qualitative conceptual review approach, ten peer-reviewed articles published between 2020 and 2025 were analyzed to identify dominant strategic patterns and emerging hybrid models. The findings reveal a growing tendency among firms to adopt hybrid strategies that align global efficiency with local relevance. Digital culture, algorithmic personalization, and cross-platform engagement emerged as key mediating factors influencing this integration. The study concludes that hybrid strategies enable firms to maintain a unified global identity while achieving cultural resonance in diverse digital environments. Theoretically, this paper enriches the standardization–adaptation discourse by highlighting digitalization as a moderating factor, while practically offering insights for global marketers seeking to optimize scalability and authenticity across international markets.